Assessment of welfare issues during traditional slaughter of goats in Pretoria, South Africa - Qekwana, D.N.; McCrindle, C.M.E.; Oguttu, J.W.; Grace, Delia; Cenci-Goga, B.T. (Informa UK Limited, 2017)
Goats are traditionally slaughtered to celebrate marriages and births, venerate ancestors, address personal problems, or perform a ritual during funerals. The objective of this study was to assess nonhuman animal welfare issues associated with the traditional slaughter of goats in and around Pretoria, South Africa. Participatory research methods were used to interview 105 respondents. Four of those interviewed were visited to observe the slaughter process. The most common method of transport was a vehicle (47%), followed by transport on foot (30%). The distance traveled (68%) was usually less than 10 km, and in all cases, it was less than 50 km. The most common (57%) method of restraining goats during transport was tying all 4 legs together. During slaughter, assistants held the head and legs of the goat (55%). Prior to slaughter, the majority of goats were tied under a tree (66%). In total, 97% of the goats were slaughtered within 24 hr, and no stunning was performed. In this study, animal welfare problems were widespread. Research should be undertaken to find practical ways to address animal welfare issues during traditional slaughter.